L-selectin ligands in human endometrium: comparison of fertile and infertile subjects - Margarit, L; Gonzalez, D; Lewis, P D; Hopkins, L; Davies, C; Conlan, R S; Joels, L; White, J O (Human reproduction (Oxford), 2009)
L-selectin ligands, localized to the luminal epithelium at the time of implantation, may support the early stages of blastocyst attachment. We have assessed the expression of two L-selectin ligands, defined by MECA-79 and HECA-452 monoclonal antibodies, and the sulfotransferase GlcNAc6ST-2, involved in generation of L-selectin ligand epitopes, in the secretory phase of the endometrium from fertile and infertile patients. Endometrial samples were obtained from 33 fertile, 26 PCOS, 25 endometriosis and 33 patients diagnosed with unexplained infertility. L-selectin ligands and GlcNAc6ST-2 expression was assessed by immunohistochemistry and immunoblotting. Immunohistochemical staining of uterine epithelium, from fertile and infertile women, demonstrated differential expression of MECA-79 and HECA-452 epitopes. In fertile women in the secretory phase MECA-79 was more strongly expressed, particularly on the lumen, than in infertile women. HECA-452 staining was significantly stronger in the glands in PCOS and endometriosis patients than in fertile women. GlcNAc6ST-2 expression was reduced in infertile patients, correlating with MECA-79 expression. This study demonstrated significant differences in expression of L-selectin ligands between fertile and infertile women in natural cycles, and could contribute to patient assessment prior to initiating fertility treatment.